2018
DOI: 10.1259/bjr.20180625
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of unresectable medium-large hepatocellular carcinoma nodules treated with radiofrequency ablation using a multiple-electrode switching system

Abstract: Avitabile G, et al. Long-term follow-up of unresectable medium-large hepatocellular carcinoma nodules treated with radiofrequency ablation using a multiple-electrode switching system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the follow-up, the OS at 4 years was 49%. 69 Another series included HCC with a median size of 9 cm treated by stereotactic RFA and reported efficacy of ablation of 80.5% with treatment-related mortality of 2.3%. Major complication rate here was 20.5%.…”
Section: Increasing the Size Of Ablated Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the follow-up, the OS at 4 years was 49%. 69 Another series included HCC with a median size of 9 cm treated by stereotactic RFA and reported efficacy of ablation of 80.5% with treatment-related mortality of 2.3%. Major complication rate here was 20.5%.…”
Section: Increasing the Size Of Ablated Lesionsmentioning
confidence: 99%
“…Mbp‐RFA treatment in HCC nodules with sizes between 3 and 6 cm in nonsurgical candidates with liver cirrhosis reported the complete ablation in all nodules without procedure‐related death or major complications. In the follow‐up, the OS at 4 years was 49% 69 . Another series included HCC with a median size of 9 cm treated by stereotactic RFA and reported efficacy of ablation of 80.5% with treatment‐related mortality of 2.3%.…”
Section: Introductionmentioning
confidence: 99%
“…6,14,15 The ablation effect was mainly enhanced by double or multiple antennas/electrodes placed simultaneously, thermal ablation combined with transarterial chemoembolization (TACE), or utilizing 3D visualization preoperative planning system to assist ablation. 6,[17][18][19] The literature reported that thermal ablation combined with TACE was superior to thermal ablation alone for liver cancer with a diameter of 3-7 cm that could not be surgically resected. [20][21][22][23] Nevertheless, these strategies increased medical expenses inevitably, and the trauma or side effects of TACE could not be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to enlarge the thermal field for RFA, to break the 3 cm tumor barrier in thermal ablation. Although multiple electrode placement [7][8][9] and RFA plus transcatheter arterial chemoembolization (TACE) 10,11 have been applied, local tumor progression (LTP) remains a challenge for large HCC. No-touch multibipolar RFA, a new technique of RFA for complete tumor necrosis, provides higher intensity energy than traditional RFA, although it remains associated with greater recurrence rates than those observed with SR in tumors larger than 3 cm 3,12 .…”
Section: Introductionmentioning
confidence: 99%